2016
DOI: 10.1530/rep-16-0330
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between FSH and relaxin at the end of the proliferative stage of rat Sertoli cells

Abstract: Follicle-stimulating hormone (FSH) stimulates the proliferation of immature Sertoli cells through the activation of PI3K/AKT/mTORC1 and MEK/ERK1/2 pathways. Mature Sertoli cells stop proliferating and respond to FSH by stimulating cAMP production. To gain insight into possible mechanisms involved in this switch as well as the impact of paracrine factors that stimulate cell proliferation, we analyzed the effects of FSH and relaxin on intracellular signaling pathways involved with proliferation and differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 62 publications
0
15
0
1
Order By: Relevance
“…The role of FSH in Sertoli cell proliferation has been largely investigated. 18,31,[38][39][40][41][42] Considering that FSH regulates Sertoli cell proliferation during fetal and postnatal life, it is important to analyze factors that might counteract FSH In the present investigation, we show that RSV suppresses FSH-stimulated Sertoli cell proliferation. As for the regulation by FSH of the regulators of G1/S cell cycle transition, it has been shown that FSH can regulate, either directly or indirectly, Sertoli cell cyclins D1 and D2 levels in different experimental models.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The role of FSH in Sertoli cell proliferation has been largely investigated. 18,31,[38][39][40][41][42] Considering that FSH regulates Sertoli cell proliferation during fetal and postnatal life, it is important to analyze factors that might counteract FSH In the present investigation, we show that RSV suppresses FSH-stimulated Sertoli cell proliferation. As for the regulation by FSH of the regulators of G1/S cell cycle transition, it has been shown that FSH can regulate, either directly or indirectly, Sertoli cell cyclins D1 and D2 levels in different experimental models.…”
Section: Discussionmentioning
confidence: 59%
“…18,31,[38][39][40][41][42] Considering that FSH regulates Sertoli cell proliferation during fetal and postnatal life, it is important to analyze factors that might counteract FSH RNA was extracted and RT-qPCR was performed. 18,31,[38][39][40][41][42] Considering that FSH regulates Sertoli cell proliferation during fetal and postnatal life, it is important to analyze factors that might counteract FSH RNA was extracted and RT-qPCR was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the hypothesis that relaxin has a role on Sertoli cell proliferation, it has been observed that KO mice for this gene have smaller testes (77). More recently, a crosstalk between FSH and relaxin at the end of the proliferative stage in rat Sertoli cells was demonstrated, and the authors postulate that whereas FSH action predominates and seems essential to direct cell maturation, relaxin seems to preferentially promote Sertoli cell proliferation (78, 79).…”
Section: Main Factors Involved In the Stimulation Of Sertoli Cell Promentioning
confidence: 99%
“…Sertoli cell proliferation is regulated by hormones, growth factors and cytokines during fetal and neonatal period of development. FSH stimulates Sertoli cell proliferation by activating cAMP/PKA/ERK1/2 and P13K/Akt/mTORC1 dependent-pathway [ 49 ]. Relaxin increases the levels of proliferating cell nuclear antigen (PCNA) in Sertoli cell cultures by activating P13K/Akt and ERK1/2 pathway [ 50 ].…”
Section: Discussionmentioning
confidence: 99%